Gale encyclopedia of multicultural America. Primary documents - Lehman, Jeffrey, 1969- (Detroit : Gale Group, 1999)
Primary documents, including letters, articles, cartoons, photos, and songs, illuminate the experience of culture groups in the U.S. from colonial times to the present.
v. 1. Afghan Americans - Italian Americans -- v. 2. Jamaican Americans - Vietnamese Americans.
Includes bibliographical references and index.
Mode of access: Internet.
Keywords: Ethnology -- United States -- History -- Sources -- Juvenile literature; Minorities -- United States -- History -- Sources -- Juvenile literature; Cultural pluralism -- United States -- History -- Sources -- Juvenile literature; United States -- Race relations -- Sources -- Juvenile literature; United States -- Ethnic relations -- Sources -- Juvenile literature